Effects of pretreatments on structural and functional changes of oat protein isolate. Issue 1 (27th September 2021) - Wang, Hailin; Xiang, Leiwen; Rao, Pingfan; Ke, Lijing; Wu, Benyang; Chen, Sheng; Wang, Shaoyun; Shi, Yuande; Su, Pingping
Abstract: Background and objectives: For most of the application of cereal materials, sample pretreatments are considered critical factors. Different pretreatments (roasting and amylase hydrolysis) prior to extraction were employed to obtain oat protein (OP) from oat grains. The effect of pretreatment on the structure and functional properties of OPs was determined. Findings: Analysis of sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS‐PAGE) revealed that the oat proteins were glycated during the roasting pretreatment and amylase hydrolysis pretreatment, of which the grafting degree was increased to 55.34 ± 0.32% by amylase hydrolysis pretreatment. These pretreatments could lead to the increase in surface hydrophobicity (H0 ) and thermal stability of OP, but reduced its emulsifying properties and solubility. In addition, the pretreatments also raised the content of α‐helix, turns, and random coil, but decreased β‐strand content. Conclusions: These results suggested that glycation induced prominent changes in the secondary and tertiary structure, including the formation of a new tertiary structure. Significance and novelty: These results are of great significance for improving the applicability of the oat pretreatment in the food industry.